Experimental Study on the Dynamic Mechanical Properties of Large-Diameter Mortar and Concrete Subjected to Cyclic Impact - Bi Sun; Yang Ping; Zhende Zhu; Zhijian Jiang; Nan Wu (Shock and Vibration)
Rock bursts are typically accompanied by multiple shocks. In order to explore the dynamic characteristics of filling materials in rock burst roadways, we employ the split Hopkinson pressure bar (SHPB) test to analyze the dynamic mechanical response of mortar and concrete under cyclical impact. The SHPB test results of the large-size specimen indicate the improvement in the waveform shape and the reduction in the wave dispersion via the application of the rubber sheet as the pulse shaper. Under cyclic impact, the peak stress and energy utilization ratio of mortar and concrete specimens were reduced, demonstrating obvious fatigue characteristics. The mortar peak stress and energy utilization ratio were observed to be sensitive to the impact times, while those of concrete were sensitive to impact pressure. The damage evolution of mortar and concrete exhibited very similar trends under the cyclic impact load, whereby the impact pressure had minimal effect on the damage evolution.